MENINGKATKAN HASIL BELAJAR SISWA KELAS X IPS MA DARUL IMAN PALU DALAM MENYELESAIKAN SOAL CERITA SISTEM SAMAAN LINEAR DUA VARIABEL MELALUI PENDEKATAN CONTEXTUAL TEACHING AND LEARNING (CTL): Improving Student Learning Outcomes Of Class X Ips Ma Darul Iman Palu In Solving Story Problems On Linear Equation Systems Of Two Variables Through The Contextual Teaching And Learning (Ctl) Approach - Fitriana; Ismaimuza, Dasa; Nurhayadi (Universitas Tadulako, 2024)
The main purpose of this study is to describe the application of the contextual teaching and learning approach in an effort to improve student learning outcomes on the material of a two-variable linear equation system. The research design refers to the research model developed by Kemmis and Mc.Taggart which consists of four components, namely (1) planning, (2) action implementation, (3) observation and (4) reflection. The data collected in the form of teacher and student activity data through observation sheets, interviews and field notes. This research was carried out using a contextual teaching and learning approach by following the following steps: (1) conveying goals and preparing students, (2) presenting information, (3) organizing students into study groups, (4) guiding group work and learning, and (5) evaluation.